2013
DOI: 10.1371/journal.pone.0057930
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Resveratrol-Enriched Rice for the Treatment of Metabolic Syndrome and Related Diseases

Abstract: Resveratrol has been clinically shown to possess a number of human health benefits. As a result, many attempts have been made to engineer resveratrol production in major cereal grains but have been largely unsuccessful. In this study, we report the creation of a transgenic rice plant that accumulates 1.9 µg resveratrol/g in its grain, surpassing the previously reported anti-metabolic syndrome activity of resveratrol through a synergistic interaction between the transgenic resveratrol and the endogenous propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 32 publications
3
73
0
1
Order By: Relevance
“…In previous report, long-term supplement of RR showed anti-obesity effects, as manifested by reduced body weights and abdominal fat volumes, without causing serious side effects . This previous study suggests that RR may be a natural source of biologically active resveratrol, showing a synergistic interaction between resveratrol and rice in the control of metabolic syndrome and related diseases (Baek et al, 2013).…”
Section: Original Articlementioning
confidence: 82%
See 2 more Smart Citations
“…In previous report, long-term supplement of RR showed anti-obesity effects, as manifested by reduced body weights and abdominal fat volumes, without causing serious side effects . This previous study suggests that RR may be a natural source of biologically active resveratrol, showing a synergistic interaction between resveratrol and rice in the control of metabolic syndrome and related diseases (Baek et al, 2013).…”
Section: Original Articlementioning
confidence: 82%
“…Our collaborative group reported that RR might act against metabolic syndrome and related diseases (Baek et al, 2013;Baek et al, 2014). Interestingly, RR shows synergistic effects in comparison that of each resveratrol or rice alone (Baek et al, 2013;Baek et al, 2014). Several reports show that resveratrol decreases the expression of tyrosinase (Franco et al, 2012;Zheng et al, 2012;Bae et al, 2013;Park and Boo, 2013;Park et al, 2014), and Jun et al reported that gamma-oryzanol from rice extract dually inhibited cellular melanogenesis, too (Jun et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In view of, about 40% of the world population consumes rice as staple food, development of rice varieties producing resveratrol which has functional value is very important (Baek et al, 2013). However, the assessment of possible changes in disease resistance should be evaluated before release of the transgenic variety to farmers.…”
Section: Assay For Possible Horizontal Gene Transfer To Pathogensmentioning
confidence: 99%
“…This study was aimed to assess the difference of disease occurrence between transgenic rice variety, Iksan526 transformed with stilbene synthase gene (Baek et al, 2013) and nontransgenic rice varieties, Dongjin and Nampyeong in the field. Moreover, in view of the concerns about the transfer of engineered DNA from genetically engineered crop to plant pathogens, we investigated the possibility of horizontal gene transfer in natural or artificial infection conditions.…”
Section: Introductionmentioning
confidence: 99%